Research on earthquake disaster risk based on the anti-lethal levels of buildings at the township level: a case study in Suqian, China - Xihai Zhang; Ting Zhang; Dongchen Wang; Chen Wang; Nian Xu; Fei Gao; Yan Deng; Xiwei Fan (Geomatics, Natural Hazards & Risk, 2025)
The assessment of earthquake disaster risk constitutes a fundamental basis for the rational allocation of disaster relief resources and the formulation of scientifically strategies for earthquake prevention and disaster mitigation. This study, through a case study conducted in Suqian City, introduces a methodology for evaluating regional earthquake disaster risk based on the analysis of the anti-lethal levels of buildings. Initially, indicators of the anti-lethal levels of buildings for three prevalent building types are identified in Suqian, including frame structures, brick-concrete structures, and brick-wood structures. Subsequently, the anti-lethal levels of buildings at 359 survey points across 98 towns in Suqian are quantified through field investigations of ‘town-to-town’. And then, the overall anti-lethal levels for each of the 98 townships are calculated. Finally, by integrating seismic hazard levels, permanent residential population, and personnel mortality matrix, the earthquake disaster risk for Suqian is comprehensively assessed. The result shows that although the overall quality and anti-lethal levels of urban buildings are better, urban areas of Suqian face higher earthquake disaster risk than rural areas due to elevated hazard potential and higher population density. The method offer more precise and actionable technical support for the development of local earthquake disaster prevention and mitigation strategies.